2020
DOI: 10.1039/c9se00942f
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically catalyzed conversion of cornstalk lignin to aromatic compounds: an integrated process of anodic oxidation of a Pb/PbO2electrode and hydrogenation of a nickel cathode in sodium hydroxide solution

Abstract: This paper presents a novel process to degrade cornstalk lignin in alkaline liquor by using an electrolytic cell, equipped with a nickel plate cathode and a Pb/PbO2 anode in sodium hydroxide solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…[108] Only limited efforts have focused on hybrid electro-oxidative and electroreductive depolymerization of lignin. [34,59,87,152,153] The advantage of a hybrid approach results from simultaneous generation of reactive oxygen species and hydrogen in situ, which can be used for electro-oxidation and electro-reduction of lignin and its intermediates. [59] Li and co-workers investigated a hybrid electrochemical degradation of bamboo lignin using a Cu cathode and Pb/PbO 2 anode in sodium hydroxide solution, [34] and identified vanillin, syringaldehyde and p-coumaric acid as the main products.…”
Section: Hybrid Electro-oxidation and Reduction Of Lignin Conversionmentioning
confidence: 99%
See 2 more Smart Citations
“…[108] Only limited efforts have focused on hybrid electro-oxidative and electroreductive depolymerization of lignin. [34,59,87,152,153] The advantage of a hybrid approach results from simultaneous generation of reactive oxygen species and hydrogen in situ, which can be used for electro-oxidation and electro-reduction of lignin and its intermediates. [59] Li and co-workers investigated a hybrid electrochemical degradation of bamboo lignin using a Cu cathode and Pb/PbO 2 anode in sodium hydroxide solution, [34] and identified vanillin, syringaldehyde and p-coumaric acid as the main products.…”
Section: Hybrid Electro-oxidation and Reduction Of Lignin Conversionmentioning
confidence: 99%
“…Most recently, Lan et al reported a novel hybrid electro-redox procedure for transforming cornstalk lignin to aromatic compounds through an anodic oxidation using a Pb/PbO 2 electrode and hydrogenation of a nickel cathode in sodium hydroxide solution. [153] As mentioned above, the Pb/PbO 2 electrode is generally utilized as an anode, with varying metals as cathodes in the lignin hybrid electro-redox procedure. A detailed description of the mechanism for the hybrid electro-redox depolymerization of lignin is shown in the electrooxidative and electroreductive lignin conversion sections of this review.…”
Section: Hybrid Electro-oxidation and Reduction Of Lignin Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards, these intermediates went through the electro-hydrogenation process at the cathodes (such as Ni, Cu, Cu/Ni-Mo-Co, alloyed Steel, Ti/Cu/Sn). In the above system, vanillin, syringaldehyde, acetosyringone, 3-hydroxy-4-methoxyphenyl-ethanone, and 4-methoxy-3-methyl-phenol were obtained as the degradation products [18,53,[58][59][60][61]. Recently, Movil-Cabrera et al [14] prepared a Co core/Pt partial shell nanoparticle alloy anode coupled with a Pt ring cathode to electrochemically degrade lignin, suggesting that the *OH generated from water electrolysis.…”
Section: Degradation Of Lignin and Lignin Model Compounds By Ros Genementioning
confidence: 99%
“…CuSO 4 is the best catalyst, and the total yield of aromatic aldehydes is as high as 24.4%, and the effect of iron salt is also good. This may be due to the promotion of oxidative degradation of wood in the process of electron gain and loss of transition metal salt ions [10].…”
Section: Effect Of Catalyst Typesmentioning
confidence: 99%